Obtaining manufacturers' perspectives in making regional transportation decisions. Issue 2 (15th March 2017) - Munnich, Lee; Douma, Frank
Abstract: The University of Minnesota's Humphrey School of Public Affairs worked with the Minnesota Department of Transportation (MnDOT), Minnesota Department of Administration, and University of Minnesota Extension to develop and implement a unique approach linking economic development and transportation planning. Using the Economic Development Administration's US Cluster Mapping tool, competitive traded industry clusters were identified in MnDOT operations districts. University, MnDOT, and local economic development staff interviewed manufacturers and their carriers within the identified clusters to understand the transportation and logistics issues these companies face and how MnDOT could make improvements to its operations and systems to help alleviate or minimize these issues. The approach was modeled after the successful business retention and expansion work conducted for Minnesota communities by the University of Minnesota Extension Center for Community Vitality. A key element to the success was involving local economic development staff in interviews and pairing them with MnDOT staff.